Examining Patients' Capacity to Use Patient Portals: Insights for Telehealth. Issue 12 (December 2021) - McAlearney, Ann Scheck; Sieck, Cynthia J.; Gregory, Megan E.; Di Tosto, Gennaro; MacEwan, Sarah R.; DePuccio, Matthew J.; Lee, Jennifer A.; Huerta, Timothy R.; Walker, Daniel M.
Abstract : Background: The increase in telehealth in response to the coronavirus disease 2019 pandemic highlights the need to understand patients' capacity to utilize this care modality. Patient portals are a tool whose use requires similar resources and skills as those required for telehealth. Patients' capacity to use patient portals may therefore provide insight regarding patients' readiness and capacity to use telehealth. Objective: The aim of this study was to examine factors related to patients' capacity to use a patient portal and test the impact of these factors on patients' portal use. Research Design and Subjects: Using data from a large-scale pragmatic randomized controlled trial of patient portal use, 1081 hospitalized patients responded to survey items that were then mapped onto the 4 dimensions of the Engagement Capacity Framework: self-efficacy, resources, willingness, and capabilities. Measures: The outcome variable was frequency of outpatient portal use. We evaluated associations between Engagement Capacity Framework dimensions and patient portal use, using regression analyses. Results: Patients with fewer resources, fewer capabilities, lower willingness, and lower overall capacity to use patient portals used the portal less; in contrast, those with lower perceived self-efficacy used the portal more. Conclusions: Our findings highlight differences in patients' capacity to use patient portals, which provide an initial understanding of factors that may influence the use of telehealth and offer important guidance in efforts to support patients' telehealth use. Offering patients training tailored to the use of telehealth tools may be particularly beneficial. Abstract : Supplemental Digital Content is available in the text.